Small Town, Big Picture: Scope of Practice of Rural Family Medicine, the Shawville Experience - Gorsky, Kevin; Safran, Tyler (McGill Journal of Medicine, 2017)
Living in the countryside, time moves a little bit slower. The people are friendly, neighbours look out for one another and denizens are grateful for the miles that separate them from the high-octane hustle of city life. When a city-slicker tries to integrate into this new world, certain dichotomies quickly emerge. For those that call small-town Canada their home, the start of hunting season is a far more prescient date than the start of the new fiscal quarter. These remarks are not a condemnation, far from it, but rather an attempt to illuminate a culture and perspective that many metropolitans have lost, if ever grasped at all. These comments certainly hold water when discussing the town of Shawville, Quebec. Though the overall ethos may be a bit humbler throughout the expansive planes of the Pontiac, the practice of medicine is anything but.